Reinterpretasi Status Minoritas Dzimmi di Tengah Mayoritas Muslim - Umar Faruq Thohir (Asy-Syari’ah : Jurnal Hukum Islam, 2020)
The territorial of Islamic dominion was become worth to be struggled in the past era of Islamic development. This circumstance divided the territorial of Islamic dominion in to dâr al-Islâm and dâr al-Harb. This divide has conceptualized a new Islamic exclusive school who has assumed that the infidels who have been in the non Islamic territorial could be battled. They think that every infidels look Moslems away and wish to battle them, even contrary, in the actually. This Islamic exclusive school also think that the governance must be led by Moslem and there is no chance for infidel to be a leader in all aspects of Islamic territorial government. The infidels always and still in the second class. Whatever, this classical thinking still alive in the mind (paradigm) of the present fiqh's scholars. If we remind to the Charter of Madinah, we can find that our prophet Muhammad never sub-ordinated the infidel. He made a charter where every Madinah's society had to obey the rules, there is no different between Moslem or infidel. In this contemporary time, where the system of territorial become a state, the sub-ordination to the infidel should be pushed away. The territorial today is stated by escaping the difference status between Moslem and infidel, because they have the same position and right to develop the state and live besides each other.